2008
DOI: 10.1142/s0192415x08006132
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Trial on Mitomycin-C/Cisplatin ± KLT in Heavily Pretreated Advanced Breast Cancer

Abstract: A randomized phase II study using mitomycin (MMC)/cisplatin (DDP) regimen with or without Kanglaite (KLT, a traditional Chinese medicine) as salvage treatment was conducted to exploit KLT's potential effects on patients with advanced breast cancer (ABC). Triweekly regimen consisted of mitomycin (8 mg/m(2)) administered intravenously on day 1, and cisplatin (25 mg/m(2)) intravenously on days 1 to 3. KLT (100 ml) was given intravenously per day on days 1 to 14 every 3 weeks. Between April 2006 and July 2007, 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The overall objective response rate was 17.5% [95]. There were no significant differences between triple therapy and control treatments in terms of objective response rate, clinical benefit rates, median time to progression, and overall survival [95]. These data indicate that Kanglaite does not cause additional benefit when it is added to the mitomycin-C/cisplatin regimen in the management of advanced breast cancer patients.…”
Section: Kanglaitementioning
confidence: 81%
See 2 more Smart Citations
“…The overall objective response rate was 17.5% [95]. There were no significant differences between triple therapy and control treatments in terms of objective response rate, clinical benefit rates, median time to progression, and overall survival [95]. These data indicate that Kanglaite does not cause additional benefit when it is added to the mitomycin-C/cisplatin regimen in the management of advanced breast cancer patients.…”
Section: Kanglaitementioning
confidence: 81%
“…Kanglaite (100 ml) was given intravenously per day on days 1 to 14 every 3 weeks. The overall objective response rate was 17.5% [95]. There were no significant differences between triple therapy and control treatments in terms of objective response rate, clinical benefit rates, median time to progression, and overall survival [95].…”
Section: Kanglaitementioning
confidence: 87%
See 1 more Smart Citation
“…It has been reported that KLT is able to inhibit cellular mitosis during the G 2 /M phase of the cell cycle and promote apoptosis via the Fas/FasL pathway (44). A phase Ⅰ study indicated that there was no marked toxicity when the KLT injection was administered at the maximum dose of 50,000 mg/day in the first cycle (45). KLT has been widely used in combination with chemotherapy for the treatment of non-small cell lung cancer.…”
Section: Shenqi Fuzheng Injectionmentioning
confidence: 99%
“…Coix seed is a Chinese herbal medicine that is used in the treatment of hypertension, arthritis, cancer metastasis, asthma, and immunological disorders [3]. The main ingredient of Kanglaite® injection (KLT) is Coix seed oil [4], and it has been widely used for cancer treatment in China [5]. …”
Section: Introductionmentioning
confidence: 99%